Pengaruh Media Booklet Terhadap Pengetahuan Remaja Putri Mengenai Stunting Di Kabupaten Probolinggo - Ulfiatun Hasanah; M. Rizal Permadi (HARENA : Jurnal Gizi, 2020)
The high prevalence of stunting in Probolinggo Regency is caused by the proliferation of early marriagesthat take place after graduating from Junior and Senior high school in Probolinggo Regency. This is caused by the level of knowledge of adolescents, especially young women is classified as low. The purpose of this study is to increase the knowledge of young women about stunting, and as a preventive proceedings so that it can prevent or even reduce the prevalence of stunting in Probolinggo Regency in the future. This research is a type of Preexperimental research with one group pretest-posttest design is conducted to Ninety nine high school students in Probolinggo Regency which are taken by using quota sampling method. The study is conducted in June 2020. The dependent variable is the level of student knowledge and the independent variable is the use of booklet. The data is analyzed by using the Wilcoxon Signed Rank Test. The results of this research are there is a difference in knowledge before and after the booklet intervention was given to the high school students, this proved by increasing in the results of the female students' posttest (p = 0,000)